Stability-indicating Ultrafast Liquid Chromatographic Method for the Estimation of Teneligliptin (Antidiabetic Agent) - Mathrusri, Mukthinuthalapati (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Teneligliptin is used for the treatment of diabetes. It is generally used to reduce hyperglycemia. A new stability-indicating reversed-phase high-performance liquid chromatography method has been developed for the determination of teneligliptin in tablets and the method was validated. Materials and Methods: Teneligliptin was analyzed using formic acid:methanol:acetic acid mixture (25:75:0.1, v/v) as mobile phase with a flow rate of 0.4 mL/min (UV detection at 245 nm). Teneligliptin was exposed to different stress conditions and the chromatographic study was continued for its stability. Results and Discussion: Teneligliptin has shown linearity 1–100 μg/mL with regression equation, y = ×95722–6775.4 correlation coefficient 0.9999. The limit of detection and limit of quantification are found to be 0.2598 μg/mL and 0.8134 μg/mL, respectively. Conclusions: It is observed that this reverse-phase ultrafast liquid chromatographic method is accurate and precise and can be used for the estimation of teneligliptin tablets.